2020
DOI: 10.1530/joe-19-0208
|View full text |Cite
|
Sign up to set email alerts
|

Elevated β-cell stress levels promote severe diabetes development in mice with MODY4

Abstract: Maturity-onset diabetes of the young (MODY) is a group of monogenetic forms of diabetes mellitus caused by mutations in genes regulating β-cell development and function. MODY represents a heterogeneous group of non-insulin-dependent diabetes arising in childhood or adult life. Interestingly, clinical heterogeneity in MODY patients like variable disease onset and severity is observed even among individual family members sharing the same mutation, an issue that is not well understood. As high blood glucose level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Additional environmental or genetic factors are clearly acting alongside PDX1 mutations in the etiology of MODY. In support of this idea, the selective, inducible inhibition of IKK/NF-κB signaling in pancreatic β-cells could induce bona fide diabetes in pre-diabetic adult Pdx1 +/ − mice 12 .…”
Section: Introductionmentioning
confidence: 86%
“…Additional environmental or genetic factors are clearly acting alongside PDX1 mutations in the etiology of MODY. In support of this idea, the selective, inducible inhibition of IKK/NF-κB signaling in pancreatic β-cells could induce bona fide diabetes in pre-diabetic adult Pdx1 +/ − mice 12 .…”
Section: Introductionmentioning
confidence: 86%
“…However, the additional deterioration of β-cell function by I kappa B kinase (IKK) / Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) inhibition enhanced transformation to rapidly progressing diabetes, characterized by hyperglycemia, low insulinemia, and decreased β-cell mass. 20 Our study demonstrated that the PDX-1 high-risk polymorphism in T2DM patients resulted in lower early phase insulin secretion levels. A human study reported that there was a decreased PDX-1 expression in human islets of patients with T2DM compared with that in non-diabetic subjects, which was a result of DNA methylation due to hyperglycemia.…”
Section: Discussionmentioning
confidence: 55%
“…Transgenics presented rapid onset of diabetes characterized by hyperglycemia, hyperinsulinemia, and loss of β-cell mass. 114 Although this is a model of diabetes, it could be potentially combined with high fat or other dietary intervention to introduce hyperlipidemia and/or obesity.…”
Section: Genetic Manipulationsmentioning
confidence: 99%